-4x+9Y=9
X-3Y=-6
--------------------
(Solve x-3y=-6 for x)
Add 3y to each side
x - 3y + 3y = -6 + 3y
x = 3 y - 6
-------------------------------
Substitute 3y - 6 for x in -4x + 9Y = 9
-4(3y-6)+9y=9
-----------------------------------
Simplify
-3y+24=9
--------------------------------------------
Add -24 on each side
-3y+24+-24=9+-24
-3y=-15
----------------------------------------------------
Now divide each side by -3
-3y ÷ -3 = -15 ÷ -3
y = 5
Now you have Y!
Now we find X
==================================================================
Substitute 5 for y in x=3y-6
x=(3)(5)-6
------------------------------------------------
Simplify
x = 9
--------------------------------------------------------------
X = 9 and Y = 5 are your answers